Sensor Fusion and Its Applications 2010
DOI: 10.5772/9972
|View full text |Cite
|
Sign up to set email alerts
|

Corner Feature Extraction: Techniques for Landmark Based Navigation Systems

Abstract: Accurate and reliable maps generated autonomously guarantees improved localization especially in GPS denied surroundings like indoor (Hough, P.V.C, 1959). The use of odometry is not sufficient for position estimation due unbounded position errors. Therefore, since office like environments consists of planar surfaces, a 2D space model is adequate to describe the robot surroundings because objects are predominantly straight line segments and right angle corners. Coincidentally, line segments and corner represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Consider a full scan of 270° as an ordered sequence of measurements points ( ) can be defined in Cartesian or in polar coordinate as follow [3]: (1) represent the angle and for the distance of point . According to (1), a segmentation can be defined as bellow:…”
Section: Segmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Consider a full scan of 270° as an ordered sequence of measurements points ( ) can be defined in Cartesian or in polar coordinate as follow [3]: (1) represent the angle and for the distance of point . According to (1), a segmentation can be defined as bellow:…”
Section: Segmentationmentioning
confidence: 99%
“…A robot is said to be fully autonomous if it is able to build a navigation map [1]. A 2D map representing the geometric feature of the robot surroundings is sufficient for the navigation of ground robot.…”
Section: Introductionmentioning
confidence: 99%
“…Landmark features should be carefully considered because the uncertainties of the landmark position can affect the case of updating the position of a mobile robot as well as other stored landmarks. For this reason, the corners in an unknown environments have been chosen as landmarks by using vision sensors as in Rosten and Drummond, 7 Shen and Wang 8 and Hwang and Song, 9 while others have used sonar or laser sensors 10,11 but without the exact calculation of the distance uncertainty and angle uncertainty of the corner landmarks.…”
Section: Introductionmentioning
confidence: 99%
“…The basis of the corner extraction is line segments’ extraction from the raw sensor data. Line features have been used successfully in many experiments, 12,13 and there have also been many methods of line extraction, including the split-and-merge, 10,14 incremental probabilistic technique 15 and Hough transform. 16 Some experiments have been done by the evaluating different line extraction methods as in Nguyen et al 17 which showed that the split-and-merge and incremental method demonstrate the best performance.…”
Section: Introductionmentioning
confidence: 99%